FINANCIAL PERFORMANCE ANALYSIS OF PT. BANK LAMPUNG USING THE CAMEL METHOD (Case Study at PT. Bank Lampung Branch in Bandar Lampung) - Syafana P., Adhista (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The local bank is named PT Bank Lampung Cabang Lampung. The main issue of this research is how PT Bank Lampung Branch's financial performance, as determined by the camel method, relates to capital, assets, control, profit, and liquidity. Finding out how PT Bank Lampung Branch's financial performance is based on the indicators of capital, assets, management, profitability, and liquidity is the objective of this study. The following is the proposed hypothesis: The financial results of PT Bank Lampung Lampung Branch are examined in terms of capital, assets, management, profitability, and liquidity. Good reputation. This study uses the standard ratio comparison technique for qualitative analysis and the financial ratio method for quantitative analysis, both developed by Bank Indonesia. The financial results of PT Bank Lampung Lampung Branch from 2019-2022 obtained an average CAR ratio of 24.94% and when compared to the standard number classified as GOOD (Healthy), the average KAP ratio was 1.99%. This conclusion is based on the results of quantitative and qualitative analysis. The average NPM ratio is 71.90%, which is categorized as GOOD (Healthy) when compared to the standard criteria. The average ROA ratio is 2.5%, which is defined as VERY GOOD (Healthy) when compared to the standard. Having an average LDR ratio of 83.06%, the ratio is considered GOOD (healthy) when compared to the standard. Consequently, healthy criteria can be used to evaluate overall financial success based on important indicators.